Intergenerational Trauma: Exploring Transmission Mechanisms in Post-Conflict Families - Amping, Donnye Rura; Adiyanti, Maria Goretti; Ludji, Irene (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Trauma due to communal conflict creates a lasting impact even after the conflict has ended. Trauma not only affects individuals who experience it directly, but also has an impact on the family and social environment, which in turn has an impact across generational boundaries. This study aims to explore and analyze the mechanisms of intergenerational trauma transmission in post-conflict families, where trauma can be transmitted both directly and indirectly through psychological, family, and social interactions. The approach used is qualitative with a case study design, involving parents who experience conflict and children who are not directly involved. Data were collected through observation and in-depth interviews, then analyzed using qualitative descriptive methods, and their validity was strengthened using triangulation of data sources. The results of the study indicate that the transmission of trauma in families occurs through two main aspects: parenting patterns and the influence of the social environment. Parenting patterns that are formed from traumatic experiences of parents after conflict, especially those that have not been handled properly, tend to be overprotective and full of strict instructions. The social environment becomes a place for children to confirm the trauma received from parenting patterns which then strengthen the transmission of this trauma. These two aspects are interrelated in forming patterns and processes of intergenerational trauma transmission.